Kinerja Pegawai dalam Meningkatkan Pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kota Gorontalo - Fidyanisa Rahmi Arif; Arifin Tahir; Yakob Noho Nani (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to determine and analyze employee performance in improving services at the Population and Civil Registration Office of Gorontalo City. Viewed from the following aspects: (1) Performance Quality, (2) Punctuality, (3) Initiative, (4) Ability, and (5) Communication. This research method uses a Qualitative Approach with a Descriptive type. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study indicate that employee performance is generally good, as seen from the existence of friendly, clear service, and the use of technology to support the administrative process. However, there are still several obstacles, especially related to limited service infrastructure and network disruptions that hinder the speed of service. From the aspect of performance quality, employees have attempted to provide services according to standards, although document errors are still found due to the lack of accuracy from the public in completing files. The timeliness of service is relatively optimal, supported by the implementation of a maximum service standard of 24 hours. From the initiative side, employees have been quite responsive to public complaints. Employees' ability to operate service applications is good. Meanwhile, the communication aspect has been running effectively through the delivery of information that is easy to understand, a persuasive attitude, and the use of supporting media such as pamphlets and banners.